Experimental study on the performance evaluation and emission reduction potential of different cookstove models using standard design parameters and testing protocols. Issue 4 (3rd July 2016) - Pal, K.; Jha, M.K.; Gera, P.; Tyagi, S.K.
ABSTRACT: This article presents the design, development, experimental evaluation and parametric study of different biomass cookstove models using different feedstock having typical characteristics. This study is based on the emission reduction potential, energy, exergy, and power output by varying the quantity of different fuel wood while following the water boiling test protocols. Although the results obtained in this article exhibits several trends, with different types and quantity of wood yet are found to be consistent and comparable with one another. However, some trends are found to be very interesting and different from those already available in the literature. These results also exhibit that a specific model performs better than others in one condition, while the other does so for other set of operating conditions. This study presented here also explores the possibility for new scientific insights in the design, development and dissemination of improved biomass cookstoves in the field of sustainable development of society.